Develop Social Media Strategy to Build Parent's Brand Awareness and Purchase Intention of Children's Educational Product Through Advertisement Approach: Study Case of Lab Buddy - Triawan, Alisha Syakira (Integrasi Sains Media, 2024)
The children's educational product industry in Indonesia is experiencing growth. As a student start-up about to launch its main product, Lab Buddy needs to develop strategies to build awareness and penetrate the market effectively. With parents increasingly seeking information about children's products on Instagram, Lab Buddy must craft a strategy to leverage Instagram to deliver promotional content that attracts the target market, highlights the value and offerings of Lab Buddy, and encourages purchase intentions. This research aims to identify an effective social media strategy for Lab Buddy. It has been found that advertisements are a potent social media method that can significantly impact the business. The study employs a quantitative approach, collecting data through questionnaires and analyzing it using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data was gathered from 205 parents of children in grades 1-3 of elementary school who are familiar with and follow children's educational brands and show concern for their children's educational development, as evidenced by their purchases of educational products. The research results indicate that entertainment and credibility positively influence perceived advertising value. Furthermore, perceived advertising value positively affects brand awareness and purchase intention for children's educational products. However, informativeness does not significantly impact the perceived value of advertising these products. Based on these findings, Lab Buddy can develop an effective promotional strategy on social media by aligning with parents' interests and behaviours on Instagram to enhance awareness and drive purchase intentions.